Introducing a Short Measure of Shared Servant Leadership Impacting Team Performance through Team Behavioral Integration - Sousa, Milton; Van Dierendonck, Dirk (Frontiers in Psychology, 2016)
The research reported in this paper was designed to study the influence of shared servant leadership on team performance through the mediating effect of team behavioural integration, while validating a new short measure of shared servant leadership. A round-robin approach was used to collect data in two similar studies. Study 1 included 244 undergraduate students in 61 teams following an intense HRM business simulation of two weeks. The following year, study 2 included 288 students in 72 teams involved in the same simulation. The most important findings were that (1) shared servant leadership was a strong determinant of team behavioural integration, (2) information exchange worked as the main mediating process between shared servant leadership and team performance, and (3) the essence of servant leadership can be captured on the key dimensions of empowerment, humility, stewardship and accountability, allowing for a new promising shortened four-dimensional measure of shared servant leadership.